Environmental Taxes in Poland and South Korea – Sharing Experiences - Szymczak, Magdalena (Podatki środowiskowe w Polsce i Korei Południowej – wymiana doświadczeń, 2023)
The article aimed to identify, to assess the environmental taxes in Poland and South Korea, and to indicate a potential area of cooperation – an exchange of experience on environmental taxes. The analysis covered data from the period 2000-2020. However, in some parts, due to the availability of data, the investigation was completed in 2014 or 2019. The research methods employed were a critical analysis of domestic and foreign literature, an analysis of Polish and Korean legal acts underpinning environmental taxes in a comparative approach, and an analysis of OECD data using simple statistical methods and benchmarking elements. Four environmental taxes were identified in Poland: an excise tax on types of products deemed harmful to the environment, a Vehicle Tax, a Forest Tax and an Agricultural Tax. In South Korea, three taxes were included: Individual Consumption Tax, Automobile Tax and Transportation, Energy, Environmental Tax. Environmental taxes in Poland and South Korea were evaluated positively, taking the fiscal and informative functions as criteria. However, it was shown that an exchange of experience would be desirable, particularly in the area of improving the implementation of the stimulating function of taxes that related to air pollution.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2023; vol. 67, nr 3, s. 72-86
Keywords: environmental taxes; Polish-Korean cooperation; sustainable finance; podatki środowiskowe; współpraca polsko-koreańska; zrównoważone finanse